Um procedimento rápido para determinação de resíduos de heptacloro, aldrin e mirex em aguardente de cana - Poleze, Luciana; Ribeiro, Maria Lúcia; Francisco, Regina Célia de Toledo; Campos, Joaquim Theodoro de Souza (Eclética Química, 1991)
.